Electrochromic Adaptability of NiOx Films Modified by Substrate Temperature in Aqueous and Non‐Aqueous Electrolytes. Issue 17 (7th March 2022) - Ding, Yilin; Wang, Mengying; Mei, Zheyue; Liu, Lei; Yang, Jiaming; Zhong, Xiaolan; Wang, Mei; Diao, Xungang
Abstract: Depending on adjusting substrate temperature during film depositing, a series of NiO x films has been prepared by magnetron sputtering. The electrochromic (EC) advantage of NiO x films modified by substrate temperature is verified. Moderate heating substrate can improve surface charge transfer (from ≈30 to ≈40 mC cm −2 ) and energy storage capacity (45% increment) without damaging other performance effectively. Considering the different electrochemical mechanisms in varied electrolytes, the EC performance of NiO x films in two electrolytes is discussed. In KOH electrolyte, NiO x films at 300 °C substrates show prominent optical modulation (≈81%) and high charge capacity (≈40 mC cm −2 ). 300 °C heating compensates for the shortage of poor stability and tedious activation. In LiClO4 ‐PC electrolyte, NiO x films can undergo long‐term cycles compared with aqueous conditions, the coloration efficiency keeps high level (≈80 cm 2 C −2 ) which means small charge quantities can drive a wide transmittance range. The cyclic discrepancy in two electrolytes can be ascribed to diverse reacted modes between electrolyte ions and NiO x films. In aqueous KOH electrolyte, EC process and activated state strongly relies on Ni 2+ distribution on films surface, while NiO x experiences two phases oxidation to get thorough coloration in PC‐Li based electrolyte. Abstract : A series of NiO x films (in 30 °C, 200 °C, 300 °C, and 400 °C substrates) are prepared by Direct Current (DC) reactive magnetron sputtering. The enhanced electrochromic performance of NiO x films is discussed in aqueous and non‐aqueous electrolytes. The activation and degradation of NiO x films in KOH electrolyte mainly depend on the new phase formation of α‐Ni(OH)2 and β‐Ni(OH)2 .